Diagnostic value of prostate- specific antigen(PSA) in diagnosis of polycystic ovary syndrome(PCOS) - ديبه آلاء; فيصل رضوان; محمد أيمن عوامة (Latakia University Journal -Medical Sciences Series, 2022)
Background: Polycystic ovary syndrome(PCOS) is the most common endocrine disorder among women in reproductive age. The importance of early diagnosis and treatment comes from the serious subsequences such as infertility, metabolic and cardiovascular disorders. until now there is no one reliable marker in diagnosis of PCOS. Objective: to find new markers that have a diagnostic benefit over existing diagnostic criteria of PCOS, so we evaluated the diagnostic value of prostate specific antigen(PSA) in diagnosis of PCOS and assessed the relationship between PSA and Ferriman-Gallway Scale(FGS) for hirsutisme. Methods:66 PCOS women and 20 control were enrolled in this study. We detected the levels of serum PSA by FEIA method and evaluated the score of FGS for each participant. Results : PSA mean SD was 0,017±0.041 ng/ml in females with PCOS which was significantly higher than control ( PSA was undetectable for all participants in control group), and there was a significant relationship between PSA and FGS for hirsutism. Conclusion: we concluded that PSA can be used in diagnosis of PCOS.